Self-Esteem in Learning-Disabled Children with ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The level of self-esteem was measured, using the Piers-Harris Self-Concept Scale, in 143 special education students at high risk for ADHD in the school year 1995, at a school district in Northern Florida.